Antimicrobial Nanostructured Assemblies with Extremely Low Toxicity and Potent Activity to Eradicate Staphylococcus Aureus Biofilms. Issue 3 (22nd November 2022) - Sun, Jing; Ma, Xutao; Li, Rongye; Lin, Min; Shu, Lilei; Chen, Xuesi
Abstract: Self‐assembled cationic polymeric nanostructures have been receiving increasing attention for efficient antibacterial agents. In this work, a new type of antibacterial agents is developed by preparing pH‐dependent nanostructured assemblies from cationic copolypeptoid poly( N ‐allylglycine)‐ b ‐poly( N ‐octylglycine) (PNAG‐ b ‐PNOG) modified with cysteamine hydrochloride ((PNAG‐ g ‐NH2 )‐ b ‐PNOG) driven by crystallization and hydrophobicity of the PNOG blocks. Due to the presence of confined domains arising from crystalline PNOG, persistent spheres and fiber‐like assemblies are obtained from the same polymer upon a heating‐cooling cycle. This allows for direct comparison of antimicrobial efficiency of nanostructured assemblies with various morphologies that are otherwise similar. Both nanostructured assemblies exhibit extremely low toxicity to human red blood cells, irrespective of the presence of the hydrophobic block. Enhanced antimicrobial performance of the fiber‐like micelles compared to the spheres, which result in high selectivity of the fibers, is shown. Notably, the fiber‐like micelles show great efficacy in inhibition of the Staphylococcus aureus ( S. aureus ) biofilm formations and eradication of the mature biofilms, superior to vancomycin. The micelles also show potent in vivo antimicrobial efficacy in a S. aureus infection mouse skin model. With a systematic study, it is demonstrated that both micelles kill the bacteria through a membrane disruption mechanism. These results imply great potential of polypeptoid assemblies as promising excellent candidates for antibacterial treatment and open up new possibilities for the preparation of a new generation of nanostructured antimicrobials. Abstract : A new type of antibacterial agents with extremely low toxicity and excellent antibacterial property by preparing pH‐dependent nanostructured assemblies are developed. The assemblies show potent activity to eradicate Staphylococcus aureus biofilms and in vivo antimicrobial efficacy in a Staphylococcus aureus infection mouse skin model.